Laboratory surveillance of H1N1 swine influenza A virus infection in patients with severe acute respiratory illness (SARI)-an institutional study - G N Ravi Prakash; K. Chakrapani; G. Swarna Latha; Surekha A.; Sailaja Sailaja; Sudhakar P. (International Journal of Medical Research and Review, 2016)
Introduction: Lower respiratory tract infections (LRTI) are a leading cause of death in developing countries and are also third leading cause of death worldwide. Influenza is an acute viral and highly contagious respiratory infection causing significant morbidity and mortality. The 2009, swine flu pandemic is caused by a novel reassorted H1N1 subtype of H1N1 influenza A virus.Objectives: The present laboratory study was conducted for the active surveillance of H1N1 swine influenza A virus infection in type C category of patients with Severe acute respiratory illnesses (SARI).Materials and Methods: In clinically suspected cases of swine flu, a total of 130 deep nasal / throat swabs were collected and inoculated into viral transport medium (Himedia labs ) and In the reference lab, samples were tested with Real time reverse transcriptase PCR for universal influenza A (inf A), swine influenza A (SWinfA) and swine H1 (SW H1) probes.Results: Among the total 130 samples, 32 are showing positive by Real time RT-PCR with a prevalence of 24.61%. In 0-5 age group, 10 were positive with prevalence of 62.5%. In total 66 were males with 12 positives (18.18 %), 64 were females with 20 positives (31.25%).Conclusion: H1N1 influenza A is a potentially infectious disease, which spreads by droplet infection, so laboratory based surveillance is necessary to know the intensity of infection, seasonal trends and epidemiological factors like variations according to gender, age and region; which is also helpful for local health authorities to take the appropriate control measures.